Effects of load and sliding velocity on wear and friction of water-lubricated DLC film - Chia, Kai Xu. (2013)
Diamond has always been well known for their beauty and the extreme tribological properties it possessed. Diamond-like carbon (DLC) is much less famous, but over the years researchers discovered its potential and placed more emphasis on it. This leads to the significant improvement to DLC film property. This project will give a systematic approach towards investigating the influence of normal load and sliding velocity on friction coefficient and wear of titanium (Ti) doped DLC film with titanium interlayer in water lubricated condition.